PERENCANAAN JALUR PEDESTRIAN KORIDOR JALAN MINANGKABAU- JALAN CINDUA MATO KOTA BUKITTINGGI SUMATERA BARAT - , PUJA KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesian urban areas tend to have problems, creating urban spaces become less humane, where supposedly healthy, safe and comfortable public spaces neglect environmental aspect and less attentive towards pedestrians as ones of the users who constantly use facilities in urban areas. Corridor exists in Jalan Minangkabau and Jalan Cindua Mato is an important corridor as it is strategically connecting areas of Jam Gadang, Taman Margasatwa and Budaya Kinantan in City of Bukittinggi. Looking at the existing condition, the corridor that acts as public space and functioned as pedestrian ways is considered less feasible for people to walk. This areaâs main problem is less pleasant condition of its pedestrian way, uneven road and incomplete street furniture in the area. Regulation regarding walkable pedestrian ways in Jalan Minangkabau and Jalan Cindua Mato entitled âJalur Badunsanakâ has very good impact to the development of Bukittinggi. This regulation is steps towards a more humanist Bukittinggi, so that its potential as central business and tourism spots will be better developed. The regulation of pedestrian ways along Jalan Minangkabau and Jalan Cindua Mato is feasibly implemented as its NPV = 3,089 and BCR = 4,007,099,763 with its Break Even Point estimated to likely be reached at the 4th year.